Neurofeedback training for executive function in ADHD children: a systematic review and meta-analysis - Xiaoke Zhong; Xiaoxia Yuan; Yuanfu Dai; Xinbi Zhang; Changhao Jiang (Scientific Reports)
Abstract Executive function deficits are commonly observed in children diagnosed with attention deficit hyperactivity disorder (ADHD). This research investigates the effectiveness of neurofeedback training (NFT) in improving executive functions among this group. Studies were meticulously selected following stringent inclusion and exclusion criteria. The quality of these studies was assessed using the PEDro scale. Seventeen RCT studies were identified, totaling 939 participants. We observed significant improvements in global executive function (p < 0.055), inhibitory control (p < 0.0001) and working memory (p < 0.05) following NFT. Notably, NFT exceeding 1,260 min was more effective in enhancing inhibitory control (p < 0.01) and working memory (p < 0.01). Additionally, the effects of NFT on inhibitory control (p = 0.05) and working memory (p < 0.01) were found to be enduring. NFT is an effective intervention for improving inhibitory control and working memory in children with ADHD. Working memory exhibits a more significant enhancement when the duration exceeds 1260 min, while inhibitory control follows closely behind. Moreover, it has a more sustained effect on working memory, alongside a notable albeit secondary effect on inhibitory control.